Human CD4+CD39+ regulatory T cells produce adenosine upon co‐expression of surface CD73 or contact with CD73+ exosomes or CD73+ cells. (August 2014) - Schuler, P. J.; Saze, Z.; Hong, C.‐S.; Muller, L.; Gillespie, D. G.; Cheng, D.; Harasymczuk, M.; Mandapathil, M.; Lang, S.; Jackson, E. K.; Whiteside, T. L.
Summary While murine CD4+CD39+ regulatory T cells (Treg) co‐express CD73 and hydrolyze exogenous (e) adenosine triphosphate (ATP) to immunosuppressive adenosine (ADO), surface co‐expression of CD73 on human circulating CD4+CD39+ Treg is rare. Therefore, the ability of human Treg to produce and utilize ADO for suppression remains unclear. Using mass spectrometry, we measured nucleoside production by subsets of human CD4+CD39+ and CD4+CD39(–)CD73+ T cells or CD19+ B cells isolated from blood of 30 volunteers and 14 cancer patients. CD39 and CD73 expression was evaluated by flow cytometry, Western blots, confocal microscopy or reverse transcription–polymerase chain reaction (RT–PCR). Circulating CD4+CD39+ Treg which hydrolyzed eATP to 5′‐AMP contained few intracytoplasmic granules and had low CD73 mRNA levels. Only ∼1% of these Treg were CD39+CD73+. In contrast, CD4+CD39negCD73+ T cells contained numerous CD73+ granules in the cytoplasm and strongly expressed surface CD73. In vitro‐generated Treg (Tr1) and most B cells were CD39+CD73+. All these CD73+ T cell subsets and B cells hydrolyzed 5′‐AMP to ADO. Exosomes isolated from plasma of normal control (NC) or cancer patients carried enzymatically active CD39 and CD73+ and, when supplied with eATP, hydrolyzed it to ADO. Only CD4+CD39+ Treg co‐incubated with CD4+CD73+ T cells, B cells or CD39+CD73+ exosomes produced ADO. Thus, contact with membrane‐tethered CD73 was sufficient for ADO production by CD4+CD39+ Treg. In microenvironments containing CD4+CD73+ T cells, B cells or CD39+CD73+ exosomes, CD73 is readily available to CD4+CD39+CD73neg Treg for the production of immunosuppressive ADO.